2015
DOI: 10.1016/j.tet.2014.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical evaluation of bis(phosphine) copper catalysts for the asymmetric alkylation of 3-bromooxindoles with α-arylated malonate esters

Abstract: An improved method for the asymetric alkylation of 3-bromooxindoles with α-arylated malonate esters is described. The asymmetric alkylation demonstrated was achieved up to 70% ee utilizing a copper(II) bis(phosphine) complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The utility of methods for indole synthesis could be broadened by considering them not only as synthetic targets, but as intermediates toward other heterocycles as well. Furthermore, mild and selective transformations of indoles may be applied to tryptophan fragments in applications such as bioconjugation. , As part of our research on new indole-related methodologies and on indole-containing natural products, we have discovered a mechanistically different sequence for oxidative fragmentation of indole and oxindole derivatives that is complementary to the prevailing synthetic and enzymatic pathways (Scheme C). This method facilitates C2–C3 bond cleavage of the oxindole ring with concomitant reaction with a nucleophile, thereby offering access to diverse heterocycles and aniline derivatives, which are unattainable by conventional biomimetic oxidations.…”
supporting
confidence: 89%
“…The utility of methods for indole synthesis could be broadened by considering them not only as synthetic targets, but as intermediates toward other heterocycles as well. Furthermore, mild and selective transformations of indoles may be applied to tryptophan fragments in applications such as bioconjugation. , As part of our research on new indole-related methodologies and on indole-containing natural products, we have discovered a mechanistically different sequence for oxidative fragmentation of indole and oxindole derivatives that is complementary to the prevailing synthetic and enzymatic pathways (Scheme C). This method facilitates C2–C3 bond cleavage of the oxindole ring with concomitant reaction with a nucleophile, thereby offering access to diverse heterocycles and aniline derivatives, which are unattainable by conventional biomimetic oxidations.…”
supporting
confidence: 89%
“…In 2009 Stoltz and co-workers introduced an enantioselective protocol for their construction from substituted 3-bromooxindoles using a copper bisoxazoline catalyst (Scheme 8). 80,81 In the presence of an amine base, the bromide-bearing stereocenter at the 3-position of 65 is ablated, generating o-azaxylylene 66an extended π-electrophilethat is attacked by the Lewis acid-bound enolate. Chirality is transferred from the ligand to generate a variety of enantioenriched 3,3-disubstituted oxindole motifs (68).…”
Section: Enantioselective Protonationmentioning
confidence: 99%
“…After the reaction conditions were screened (see Table S1 in the Supporting Information for details), we were pleased to find that, with copper–bis­(oxazoline) complex [Cu] as the catalyst and N , N -diisopropylethylamine (DIPEA) as the base, the reaction of 11 with dimethyl malonate in dichloromethane at −20 °C furnished the desired product (−)- 12 in 65% yield with 91% ee. The R -configuration of the quaternary all-carbon stereocenter was also firmly established on the basis of Stoltz’s report . Interestingly, our attempt to purify the compound by recrystallization in ethyl acetate/petroleum ether (1:10) revealed that the crystals were all racemic.…”
Section: Results and Discussionmentioning
confidence: 62%
“…The C2 side chain in A could be stitched by Suzuki coupling of the 3 H -indol-2-yl triflate derived from oxindole B . Finally, the all-carbon quaternary stereocenter in B could be introduced by copper-catalyzed enantioselective malonate addition to 3-bromooxindole C , an elegant method developed by the Stoltz group …”
Section: Results and Discussionmentioning
confidence: 99%